The Cruelty of Kin: Rejection and Abjection in Rebecca Brown's Representations of Parent-Child Relationships - Xhonneux, Lisa (Miscelánea: A Journal of English and American Studies, 2014)
The work of the contemporary lesbian author Rebecca Brown can be read as a dramatization of the chosen nature of biological kinship ties –ties that are, in popular belief as in academic circles, still often considered “natural” and, therefore, dependable. Focusing on familial homophobia brings to the fore this element of choice: several of Brown’s lesbian protagonists find the “enduring solidarity” that anthropologist David Schneider famously attributed to the biological family radically contested. Brown further dissolves the naturalness of biological kinship through horrifying descriptions of childbirth, and through portrayals of her mother characters’ lack of attachment to their babies. Presenting these infants as abjects, Brown also steers clear of the passivity of the motherly “vessel” that is apparent from standard theoretical accounts on abjection, which inevitably relegate the mother’s body to the realm of the abject. Many of the babies of her lesbian protagonists, moreover, grow up to be monstrous kids. Thus Brown can be seen to contest the idea of the saintly child as our hope for the future for which everything has to be done –an ideology Lee Edelman has termed “reproductive futurism”, and which is frequently used against queers, whose sexuality is deemed incompatible with futurity.
Keywords: Rebecca Brown; Biological kinship; Familial homophobia; Abjection; Reproductive futurism